Unusual opecoelids from Red Sea triggerfishes with special reference to characteristic concepts of the Opistholebetinae Fukui, 1929 (Digenea: Opecoelidae) - Karar, Yasser F. M.; Blend, Charles K.; Mohamadain, Hoda S.; Khalifa, Refaat M. A.; Dronen, Norman O. (Zootaxa, 2020)
Three digeneans belonging to the Opecoelidae are reported and described from triggerfishes (Tetraodontiformes: Balistidae) collected in the northern Red Sea off Egypt. Both Macvicaria longicirrata (Manter, 1963) Aken-Ova, Cribb & Bray, 2008 and Neopycnadena tendu (Bray & Justine, 2007) n. comb. were recovered from the intestine of the titan triggerfish, Balistoides viridescens (Bloch & Schneider)—each represents a new host record—and Gaevskajatrema balistes n. sp. was found parasitizing the lower intestine of the Picasso triggerfish, Rhinecanthus assasi (Forsskål). We continue to support synonymy of Gaevskajatrema ponticum (Koval, 1966) Machkevsky, 1990 with Gaevskajatrema perezi (Mathias, 1926) Gibson & Bray, 1982, not as a differentiated species. We adopt the restricted posterior extension of the ceca and vitellarium to the testicular zone, without extension of either into the post-testicular space, as diagnostic in distinguishing Gaevskajatrema. Gaevskajatrema balistes n. sp. differs from G. perezi based on its substantially smaller body size with fewer eggs, a longer cirrus-pouch reaching ovarian level and it parasitizes a distinct host group from a structurally and ecologically different ecosystem. Neopycnadena n. gen. is erected for Pseudopycnadena tendu Bray & Justine 2007 based on its possessing a large broadly oval cirrus-pouch with a massive field of prostatic cells occupying the entire volume of the cirrus-pouch, a wide, cup-shaped and thick-walled ejaculatory duct, distinct dorsal position of the excretory pore, the bifurcal dextral position of the genital pore, its report from a distinct host group and distant locality and its phylogenetic uniqueness compared with Pseudopycnadena fischthali Saad-Fares & Maillard 1986. Neopycnadena n. gen. is ecologically similar to opistholebetines in their life-cycles and morphology; however, phylogenetically separate from opistholebetines as well as from the Polypipapiliotrematinae Martin, Cutmore & Cribb in Martin, Sasal, Cutmore, Ward, Aeby & Cribb, 2018 and members of Clade [C] of Martin and colleagues, thus we conclude that Neopycnadena n. gen. is unique. Neopycnadeninae n. subfam. is proposed to accommodate Neopycnadena n. gen. We consider that the probable characterization of tetraodontiform specialist taxa (as indicated by the presence of a muscular post-oral ring) and the specificity of the Opistholebetinae Fukui, 1929 sensu stricto with a tetraodontiform host are no longer reliable characters differentiating Gaevskajatrema and Macvicaria Gibson & Bray, 1982. The nature of the post-oral structure is discussed and it is adopted to be a diagnostic feature at the generic level among taxa of the Opistholebetinae sensu latu. It is concluded that the expanded concept of the Opistholebetinae is more supported than the restricted one, Birendralebes Srivastava & Ghosh, 1972 remains incertae sedis within the Opecoelidae Ozaki, 1925 rather than in the Opistholebetinae, and we provide a generic key to the Opistholebetinae.